Phenolic profile and bioactive properties of carissa macrocarpa (Eckl.) A.DC.: An in vitro comparative study between leaves, stems, and flowers - Souilem, Fedia (2018)
The present work aimed to characterize leaves, stems, and flowers of Carissa macrocarpa (Eckl.) A.DC., by performing an analysis of the phenolic compounds by HPLC-DAD/ESI-MS, correlating them with bioactive properties, such as antioxidant, anti-inflammatory, cytotoxic, and antimicrobial activities. Thirty polyphenols were identified in the hydroethanolic extract, including phenolic acids, flavan-3-ols, and flavonol glycosides derivatives (which presented the highest number of identified compounds). However, flavan-3-ols showed the highest concentration in stems (mainly owing to the presence of dimers, trimmers, and tetramers of type B (epi)catechin). Leaves were distinguished by their high antioxidant and anti-inflammatory activities, as well as their bactericidal e ect against E. coli, while stems presented a higher cytotoxic activity and bactericidal e ect against Gram-positive bacteria. Moreover, a high correlation between the studied bioactivities and the presence of phenolic compounds was also verified. The obtained results bring added value to the studied plant species.